Patient satisfaction and associated factors among insured and uninsured patients in Deder General Hospital, eastern Ethiopia: a facility-based comparative cross-sectional study - Shure, Giduma; Gamachu, Mulugeta; Mitiku, Habtamu; Deressa, Alemayehu; Eyeberu, Addis; Mohammed, Fethia; Zakaria, Hamdi Fekredin; Ayana, Galana Mamo; Birhanu, Abdi; Debella, Adera; Mussa, Ibsa (Frontiers in Medicine, 2023)
Background Patient satisfaction is a crucial measure of healthcare quality, as dissatisfied patients are more likely to miss appointments, disregard treatment plans, and leave hospitals, leading to poor treatment outcomes. Therefore, the study aimed to compare levels of satisfaction with health services and associated factors among insured and uninsured patients in Deder General Hospital, eastern Ethiopia. Methods A comparative cross-sectional study with 532 participants was conducted from December 1–30, 2021. Data was collected through a structured questionnaire, analyzed using SPSS, and predictors assessed using a multivariate logistic regression model. Statistical significance was set at p < 0.05. Results Overall, patient satisfaction with health services was 65.6% (95% CI: 61.5–69.5), and the level of patient satisfaction with health services among insured and noninsured patients was 68.8% (95% CI: 62.8–74.4) and 62.4% (95% CI: 56.8–68.0), respectively. In the final model of multivariable analysis, factors such as educational status of secondary school (AOR = 4.90; 95% CI: 2.05–11.76), and a higher level (AOR = 3.08; 95% CI: 1.05–9.03), getting the entire prescribed drugs (AOR = 3.49; 95% CI: 1.43–8.54), getting some of the ordered drugs (AOR = 3.34; 95% CI: 1.61–6.94), paying less than 100 Ethiopian birrs (AOR = 4.85; 1.35–17.40) were significantly associated with patient satisfaction among insured patients. Whereas getting the entire and some prescribed drugs were (AOR = 6.28; 95% CI: 3.26–12.05), and (AOR = 3.40; 95% CI: 1.70–6.78) times more likely to be satisfied with the service among noninsured patients as compared to their counterparts, respectively. Conclusion The study found that about six in 10 patients in the study area were satisfied with healthcare services, with insurance patients reporting higher satisfaction. Factors such as receiving prescribed drugs, paying less than 100 Ethiopian birr, having a secondary school education, and having a higher education were associated with satisfaction.